Study of temperature rise in small brushed DC motor components under different speed - Nurul Fatimah, Abdullah; Abbas, A. Wahab; Mohd Azri Hizami, Rasid (IOP Publishing, 2019)
Each electric motor has a temperature rating that is related to the insulation grade of its winding. Exceeding the maximum temperature will lead to motor destruction. In this study, the temperature rise of components in a 250W brushed DC motor including the brush, bearing, permanent magnet and casing are observed as the speed of the motor changes. Knowing that the speed is proportional to the voltage supplied, the temperature of these components was observed at voltages ranging from 8 to 24 V with no load. The results show that despite running without load, the current increase proportionally due to resistance torque that increases with the speed. The maximum temperature attained in the brush at the maximum speed tested at 55°C. The following orders are the bearing, casing and permanent magnet. The order are the same regardless the speed level.